New Splicing Mutations in the Human Factor XIIIA Gene, Each Producing Multiple Mutant Transcripts of Varying Abundance - Anwar, Rashida; Miloszewski, Krzysztof J. A.; Markham, Alexander F. (Thrombosis and Haemostasis, 1998)
Coagulation factor XIII, a transglutaminase which stabilises blood clots by covalently cross-linking fibrin, is essential for normal haemostasis. FXIII deficiency results in a life-long bleeding disorder with added complications in wound healing and tissue repair. Sequence changes in the human FXIIIA gene, largely missense mutations, are primarily responsible for inherited FXIII deficiency. We have carried out molecular analysis of the FXIIIA gene in two unrelated FXIII deficient individuals and identified three splice site mutations; a g→a at the exon 6 acceptor splice site, a g→a at the exon 7 donor splice site and a coding sequence T→G at the exon 8 donor splice site. We have also examined the FXIIIA mRNA in these patients and find that each mutation gives rise to multiple transcripts which vary in their relative abundance. The precise molecular mechanisms which result in these variant transcripts, and their relative abundance in our FXIII deficient patients, are discussed.